2021
DOI: 10.21203/rs.3.rs-384292/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Study of SARS-COV-2 Outbreaks in US Federal Prisons: the Linkage Between Staff, Inmate, and Community Transmission

Abstract: BackgroundSince the novel coronavirus SARS-COV-2 was first identified to be circulating in the US on January 20, 2020, some of the worst outbreaks have occurred within state and federal prisons. The vulnerability of inmate populations, and the additional threats posed to the health of prison staff and the people they contact in surrounding communities underline the need to better understand the dynamics of transmission in the inter-linked inmate/staff/community sub-populations to better inform optimal control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous work [61] identified an effect of countywide COVID-19 case rates on prison cases. Research incorporating both staff and resident cases [62,63] found an association between community cases and staff cases, and between staff and resident cases, in US federal prisons, and recommended containment among staff to stem introductions of COVID-19 and other diseases into prisons. Reduction of prison populations by decarceration was found to decrease the risk of COVID-19 infection in federal prisons [63,64].…”
mentioning
confidence: 99%
“…Previous work [61] identified an effect of countywide COVID-19 case rates on prison cases. Research incorporating both staff and resident cases [62,63] found an association between community cases and staff cases, and between staff and resident cases, in US federal prisons, and recommended containment among staff to stem introductions of COVID-19 and other diseases into prisons. Reduction of prison populations by decarceration was found to decrease the risk of COVID-19 infection in federal prisons [63,64].…”
mentioning
confidence: 99%